Detection of bacteria using antimicrobial polymer derived via ring-opening metathesis (romp) pathway - Suer, N. Ceren; Arasoglu, Tulin; Cankurtaran, Husnu; Okutan, Mustafa; Gallei, Markus; Eren, Tarik (Tubitak Scientific & Technological Research Council Turkey, 2021)
There is growing interest in the detection of bacteria in consumables, for example, in the food and water sectors. In this study, the aim was to produce a polymer-based bacteria biosensor via ROMP (ring opening metathesis polymerization). In the first part of the study, block and random copolymers were synthesized, and their biocidal activities were tested on the glass surface. Interdigitated electrode arrays coated with the polymers possessing the highest activity were used to screen the affinity towards different bacterial strains by monitoring impedance variations in real-time. The polymer-coated electrode could detect gram-positive and gram-negative bacteria strains at a concentration of 10(7) cfu/mL. The results show that ROMP-based polymer offers bacterial detection and can be used in developing biosensor devices for efficiently detecting pathogenic bacteria.
Keywords: Sensors; bacteria; electrical properties; antimicrobial polymer; ROMP; ESCHERICHIA-COLI; ANTIBACTERIAL POLYMERS; PATHOGENIC BACTERIA; RAPID DETECTION; PEPTIDE; IMPEDANCE; PHOSPHONIUM; COPOLYMERS; NANOMATERIALS; RECOGNITION; Chemistry; Engineering